A Practical Approach to Well-being Based Policy Development: What Do New Zealanders Want from Their Retirement Income Policies? - Joey Au; Andrew Coleman; Trudy Sullivan (New Zealand Government, The Treasury, 2015)
This paper investigates the practicality of using a sophisticated multi-criteria analysis technique to estimate the preferences of a representative sample of the public to inform policy advice. Our application concerns retirement income policy and we use a multicriteria decision-making survey to (i) investigate the relative importance of seven aspects of retirement income policies to a sample of 1,066 New Zealanders, (ii) document the diversity of policy preferences in a statistically rigorous manner, and (iii) evaluate the way people rank three different retirement income policies from an individual well-being perspective. The results of the paper suggest that multi-criteria surveys as a tool have considerable potential to help policymakers develop and identify policies that are aligned with the way people want to live. In terms of retirement income policies, we find that (i) there is widespread opposition to means-testing, (ii) a majority of respondents would choose an increase in current taxes if this could prevent even larger tax increases on future generations, and (iii) there are strongly divergent preferences over the appropriate eligibility age for New Zealand Superannuation. Overall, a policy combination that raises the age of eligibility for New Zealand Superannuation and reduces future tax increases is opposed by many and preferred by few. However, a policy that more aggressively prefunds New Zealand Superannuation by immediately raising taxes is supported by a majority of people of all ages and income groups.
Keywords: H55; I31; I39; J26; 330; Altersvorsorge; Sozialer Indikator; Multikriterielle Entscheidungsanalyse; Neuseeland